A study of the interaction between soil and the pneumatic wheels of agricultural gantry systems - Volodymyr Bulgakov; Jüri Olt; Volodymyr Kuvachov; Mykhailo Chernovol; Mykola Sviren; Serhii Kolomiiets (Agraarteadus, 2020)

(untitled)
At the stage at which agricultural gantry systems are being designed, developed, and studied, the question of a rational choice of tyres for such systems is relevant, as tyres are the most important part of an agricultural gantry system and have a significant effect on most of its operating properties. The methods that can be used for choosing tyres for traditional mobile-powered equipment are already well established by scientific experience, but the movement of agricultural gantry systems in permanent artificial tracks creates somewhat different conditions and demands for a pneumatic tyre when compared to a traditional tractor moving along agricultural soil. This is why the development of methods that will assist in finding rational parameters for the pneumatic tyres of agricultural gantry systems that are moving along compacted soil in permanent artificial tracks is an urgent and relevant task. The purpose of the study is to optimise the parameters for the tyres of agricultural gantry systems in terms of their being able to travel on compacted soil in permanent artificial tracks. Theoretical studies and the synthesis of the parameters for a pneumatic wheel to work with an agricultural gantry system took place by modelling on a PC the performance conditions of such a vehicle. The basis for the study methods was formed by the fundamentals of tractor theory and theoretical mechanics, using the software program Mathcad. The traction factor of an agricultural gantry system's pneumatic wheel was used as the performance criterion for the effectiveness of the work being done by the wheel. The physical object of study was an agricultural system that has been developed by us. As a result of the study, it was determined that the solving of the task that has been set out - using an analysis of partial derivates of the function of the efficiency of an agricultural gantry system's wheel – makes it possible to quickly and effectively determine the rational optimum points for its pneumatic tyre's parameters. It was determined that, for the agricultural gantry system at hand, and in view of the maximum efficiency of its pneumatic wheel, the wheel's tyre width must be within the range of 0.20–0.30 m and its diameter must be within the range of 0.90–1.25 m. With those ranges, it is recommended that the tyre's inflation pressure be increased from 100 kPa to 160 kPa because the partial derivates of the function of the efficiency at those parameters would decrease to near zero. It has been proven that the choice of tyre type for agricultural gantry systems should be based first on the choice of its width and then its load-bearing capacity – its diameter. The proposed methods for finding rational parameters for pneumatic wheels make it possible to determine the tyre parameters for all kinds of agricultural gantry systems which will be required to travel on compacted soil in permanent artificial tracks. For the agricultural gantry system that has been developed by us, using tyres of the 9.5R32 type provides the highest levels of efficiency, i.e. at a factor of 0.86.